Helen : the ultimate oomph of bollywood - Basil Hans V (Ghaziabad P&P Academy, 2025)
Helen story is not just about the dazzle of her performances but also about the indomitable spirit that carved a niche in an era dominated by traditional narratives. Her presence in films brought a unique blend of exotic allure and artistic exuberance, making her an icon of style and grace. She redefined the role of the vamp in Indian cinema. turning it into an art form that audiences embraced with admiration and awe.
Keywords: Motion Fictures